Avaliação de serviços de atenção básica: atualização e validação do instrumento QualiAB - Zarili, Thais Fernanda Tortorelli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Primary Health Care (PHC) has a strategic function in the construction of a universal health care system. The quality of services is now one of the major challenges to be faced by PHC, which highlights conducting evaluation surveys and quality monitoring as part of the field of management and planning in health. The QualiAB tool is an instrument that evaluates the organization of the work process through care indicators' and management PHC units. It was developed and applied in 2007 and reapplied in 2010 in São Paulo state. Although it has demonstrated reliability and validity, it requires periodic updates compromised to the continuous increase in quality. The aim of this study is to analyze comparatively between 2007 and 2010 applications and to describe and analyze the process of updating and validation of this tool as a product having an updated version and validated for national implementation. The methodology consists of sequential steps and iterative: comparative analysis between 2007 and 2010 applications; update issues, criteria, standards and indicators for peer review to define a draft, which was submitted to the pretest in 30 selected services; new review with obtaining a second version which was submetted consultation by group of experts and pilot application in a region of the São Paulo state; data analysis to define the version for national implementation. As a result is in the comparative analysis of the previous applications 5 indicators of Management and 17 Assistance, as well as the set of respondents units had p< 0.05. We obtained initially an instrument peer reviewed (QAB1) used for consultation in the pre-test with 111 questions, 17 of which are descriptive and 94 scored. The second version (QAB2) has 126 questions, with 21 questions and 105 descriptive scored and was evaluated by a group of experts through modified Delphi technique, held in two rounds. The results were compared with a pilot application in a ...

A Atenção Primária à Saúde (APS) tem papel estratégico na construção de um sistema de saúde universal. A qualidade dos serviços representa hoje um dos grandes desafios a ser enfrentado pela APS, o que coloca em destaque a realização de pesquisas de avaliação e monitoramento da qualidade, como parte do campo da gestão e planejamento em saúde. O Questionário QualiAB é um instrumento que avalia a organização do processo de trabalho por meio de indicadores de assistência e gerenciamento de unidades de APS. Foi desenvolvido e aplicado em 2007 e reaplicado em 2010 no estado de São Paulo. Embora tenha demonstrado confiabilidade e validade, requer atualizações periódicas comprometidas com o contínuo incremento da qualidade. Os objetivos desse trabalho consistem em apresentar uma análise comparativa das aplicações anteriores do instrumento e descrever e analisar o processo de atualização e validação desse instrumento tendo como produto uma versão atualizada e validada para aplicação nacional. A metodologia é composta por etapas sequenciais e iterativas: análise comparativa feita por variação percentual, teste do qui-quadrado de tendência para os indicadores e teste de mediana para o conjunto de unidades; para a atualização de questões, critérios, padrões e indicadores, houve revisão por pares para definir uma versão preliminar, pré-teste em 30 serviços escolhidos; nova revisão com obtenção de uma segunda versão a qual foi sumetida à consulta por grupo de especialistas e aplicação piloto em uma região do interior do estado de São Paulo; análise dos dados para definição da versão para aplicação nacional. Como resultados obteve-se na análise comparativa das aplicações anteriores 5 indicadores de Gerência e 17 de Assistência, assim como o conjunto de unidades respondentes obtiveram nível de significância maiores que 0,05. Para atualização do questionário, inicialmente um...
Evalution of primary care services: update and validation of the instrument QualiAB
Keywords: Cuidados primários de saúde; Indicadores de qualidade em assistência à saúde; Estudos de validação; Serviços de saude - Avaliação; Saúde pública; Primary health care